2004
DOI: 10.1074/jbc.m313474200
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of Binding Sites of Human Matrix Metalloproteinases

Abstract: Tissue components hydrolyzing matrix metalloproteinases (MMPs) exhibit a high sequence similarity (56 -64% in catalytic domains) and yet a significant degree of functional specificity. The hexapeptide-binding sites of 24 known human MMPs were compared in terms of their force field interaction energies with five probes that are most frequently encountered in substrates and inhibitors. The probes moved along a grid enclosing partially flexible binding sites in rigid catalytic domains that were represented by pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 41 publications
3
71
0
1
Order By: Relevance
“…Nonetheless, most MMPIs lack specificity with only a few able to spare the shallow S 1 0 pocket MMPs by incorporating bulky or long side chains at P 1 0 (Overall and Kleifeld, 2006). Perhaps not surprisingly, the antitarget MMPs 3, -8, -9 and also -12, a potential antitarget (Overall and Kleifeld, 2006), have similar binding properties in the active site (Lukacova et al, 2004). Comparative modeling reveals that the void volumes of the MMP antitarget S 1 0 pockets are very similar in size and shape ( Figure 1B).…”
Section: Smentioning
confidence: 99%
“…Nonetheless, most MMPIs lack specificity with only a few able to spare the shallow S 1 0 pocket MMPs by incorporating bulky or long side chains at P 1 0 (Overall and Kleifeld, 2006). Perhaps not surprisingly, the antitarget MMPs 3, -8, -9 and also -12, a potential antitarget (Overall and Kleifeld, 2006), have similar binding properties in the active site (Lukacova et al, 2004). Comparative modeling reveals that the void volumes of the MMP antitarget S 1 0 pockets are very similar in size and shape ( Figure 1B).…”
Section: Smentioning
confidence: 99%
“…Remaining MMPs were superimposed on MMP-7 as described previously. 31 Superimposed TACE and MMP-7 structures exhibit an almost perfect overlap of the backbones in individual subsites, except S3 subsite (Figure 2). However, the residues forming individual subsites have considerable effect on the overall shapes of the binding sites.…”
Section: Structures and Superpositionmentioning
confidence: 99%
“…The probe was placed in each of the grid points, and the Tripos force-field interaction energy35 , 36 was calculated for individual partially flexible binding sites. 31 The interaction energies were compared with two goals: (i) to identify the MMPs and their subsites that are most similar to TACE and (ii) to delineate the properties of the regions responsible for specific interactions of TACE with individual probes.…”
Section: Comparison Of Interaction Energies For Different Enzymesmentioning
confidence: 99%
“…4−9 Most MMP inhibitors to date developed consist of a zinc-binding group (ZBG), which binds the catalytic metal ion, 5,8,10 and a peptidomimetic backbone, which interacts noncovalently with the active site of the enzyme. 7,11 The peptidomimetic Batimastat (BB-94) is a first generation MMP inhibitor that contains the most common ZBG, that is, a hydroxamate moiety.Because of the difficulty in neutralizing locally acting SVMPs by antivenoms, the possibility has been raised that specific enzyme inhibitors may represent a new alternative for the treatment of these envenomations. 12 At the experimental level, it has been shown that chelating agents, such as EDTA salts, as well as Batimastat, are effective at inhibiting both the isolated SVMPs and the hemorrhagic activity of crude viperid venoms in animal models, 13,14 underscoring the potential therapeutic value of such inhibitors in this pathology.…”
mentioning
confidence: 99%
“…4−9 Most MMP inhibitors to date developed consist of a zinc-binding group (ZBG), which binds the catalytic metal ion, 5,8,10 and a peptidomimetic backbone, which interacts noncovalently with the active site of the enzyme. 7,11 The peptidomimetic Batimastat (BB-94) is a first generation MMP inhibitor that contains the most common ZBG, that is, a hydroxamate moiety.…”
mentioning
confidence: 99%